Study of respiratory syncytial virus infection in children below two years of age with acute lower respiratory tract infection. - Wicramasinghe, G (My University, 1996)
This study was designed to identify the causative viral agents with particular refernce to respiratory syncytial (RSV) in children less than 2 years of age with lower respiratory tract infections.Direct fluorescent antibody test was found to be a sensitive and rapid diagnostic test for the detection of repiratory syncytial virus.The results could be made available on the same day and as such this test would be most valuable in the management of the patients.The unnecessary use of antibiotics could be avoided and messure could be taken to control the spread of the infection in the ward. patients.